THE INFLUENCE OF FINANCIAL LITERACY, SELF-CONTROL AND RELIGIOSITY ON CONSUMPTIVE BEHAVIOR (UMSIDA Student Case Study Program in Financial Management of 2022 - Muhamad Sabiqi Sulaiman; Sri yono; Herlinda Maya Kumala Sari (UNIVERSITAS MUHAMMADIYAH METRO, 2025)
The purpose of this study was to determine how the behavior of UMSIDA Financial Management Study Program Batch 2022 students as consumers in relation to financial literacy, self-control, and religion. Ninety-seven students of the UMSIDA Financial Management Study Program Batch 2022 were used as research respondents. SPSS 22 software was used as an analytical tool, and statistical calculations were carried out in the form of validity and reliability tests. Traditional assumption tests (heteroscedasticity, multicollinearity, and normality tests), multiple linear regression analysis, and hypothesis testing in the form of t, F, and coefficient of determination (RÂ²) tests are some of the techniques used in data analysis. The study findings on financial literacy have a major impact on the way people shop. Consumer behavior is strongly influenced by self-control. Religiosity has a significant effect on consumptive behavior. Simultaneously financial literacy, self-control and religiosity have a significant effect on consumptive behavior.